Corporate governance and the bankrupt firm: An empirical assessment - Daily, Catherine M.; Dalton, Dan R. (Strategic Management Journal, 1994)
Abstract The incidence of bankruptcy has risen dramatically among firms of all types and sizes in the past decade. Little is known, however, about the effects of alternative governance structures on the propensity of an organization to file Chapter 11 bankruptcy. Relying on logistic regression for periods 5 years and 3 years prior to the bankruptcy, as well as the contemporaneous period, we examine the relationships among independent/interdependent board composition and the structure of CEO/board chairperson positions and the filing of bankruptcy. While controlling for a series of financial indicators and firm size, the results illustrate robust explanatory power for the governance variables for both lagged periods.